2012
DOI: 10.1007/s10571-012-9900-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of N-Acetyl-Glucagon-Like Peptide-1 in Primary Motor Neuron Cultures Derived From Non-Transgenic and SOD1-G93A ALS Mice

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the death of motor neurons (MN) in the motor cortex, brain stem, and spinal cord. In the present study, we established an ALS in vitro model of purified embryonic MNs, derived from non-transgenic and mutant SOD1-G93A transgenic mice, the most commonly used ALS animal model. MNs were cultured together with either non-transgenic or mutant SOD1-G93A astrocyte feeder layers. Cell viability following exposure to kainate as exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…This hypothesis is also consistent with the finding that another widely used anti-diabetic drug, metformin, was associated with worse neurological scores and faster symptom progression in female SOD1 mice in a dose-dependent manner [25]. However, another class of anti-diabetics, glucagon-like peptide 1 (GLP-1) analogs, has demonstrated neuroprotection against Kainate-induced excitotoxicity and trophic-factor withdrawal in SOD-1 in vitro and in vivo models [26-27]. The generalizability of this data is currently limited because of lack of reproducibility in ALS-TDP model, besides the fact that there was no viability/survival assessment under the oxidative stress induced by SOD-1 mutation itself.…”
supporting
confidence: 79%
“…This hypothesis is also consistent with the finding that another widely used anti-diabetic drug, metformin, was associated with worse neurological scores and faster symptom progression in female SOD1 mice in a dose-dependent manner [25]. However, another class of anti-diabetics, glucagon-like peptide 1 (GLP-1) analogs, has demonstrated neuroprotection against Kainate-induced excitotoxicity and trophic-factor withdrawal in SOD-1 in vitro and in vivo models [26-27]. The generalizability of this data is currently limited because of lack of reproducibility in ALS-TDP model, besides the fact that there was no viability/survival assessment under the oxidative stress induced by SOD-1 mutation itself.…”
supporting
confidence: 79%
“…Recent research showed that GLP-1R has the promising ability to generate neuroprotection against neurological disorders, including Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS) and ischaemic stroke1819. Although many new drugs have been demonstrated to have a significant neuroprotective ability based on laboratory results, these candidate drugs have not been approved by clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two antidiabetic drugs, metformin and pioglitazone, seem to have no beneficial effect in the SOD1 G93A mouse model of ALS (Kaneb et al, 2011) and a clinical trial (Dupuis et al, 2012;Jawaid et al, 2014). However, another class of antidiabetic drugs, GLP-1 analogues, has demonstrated neuroprotection against kainate-induced excitotoxicity and trophic factor withdrawal in SOD1 in vitro and in vivo models (Lim et al, 2010;Li et al, 2012b;Sun et al, 2013).…”
Section: Alsmentioning
confidence: 99%
“…Moreover, a study showed that exendin-4 protects motor neurons against glucosamine-induced cytotoxicity by restoring cellular glucose uptake, glucokinase activity, and intracellular ATP levels (Lim et al, 2010). Similarly, N-acetyl-GLP-1(7-34) amide (N-ac-GLP-1), a long-acting, N-terminally acetylated, C-terminally truncated analogue of GLP-1, also showed therapeutic potential in primary motor neuron cultures derived from nontransgenic and SOD1 G93A ALS mice (Sun et al, 2013). Thus, these neuroprotective effects of exendin-4 and N-ac-GLP-1 support the concept that GLP-1 signaling is neuroprotective and may be a treatment strategy for ALS.…”
Section: Effects Of Glp-1 On Neurodegenerative Diseasementioning
confidence: 99%